Green Logistics and Transportation A Sustainable Supply Chain Perspective - Fahimnia, Behnam; Bell, Michael G.H; Hensher, David A.; Sarkis, Joseph (Greening of Industry Networks Studies, 2015)
This book identifies and furthers the state of the art in green logistics and transportation with a supply chain focus. It includes discussions on concerns and linkages across policy, corporate strategy and operations, and inter-organizational relationships and practices. Separate sections are assigned to discuss issues related to greening of logistics and transportation functions, including green logistics network, green land transportation, and green air and water transportation. Linking research with practice is another important feature of the book as various techniques and research methodologies are utilized to explain and analyze green logistics and transportation concepts and issues. The authors come from throughout the world from a variety of backgrounds (e.g. policy, technical, engineering, and management backgrounds) to provide solutions and insights from their regional and global perspectives to some of the world's most critical green logistics and transportation issues.